Comparison of operator line-of-sight (LOS) assessment techniques: evaluation of an underground load-haul-dump (LHD) mobile mining vehicle - Synopsis - J. West (The Southern African Institute of Mining and Metallurgy, 2007)
For many years line-of-sight (LOS) issues for underground mobile equipment is a growing focus of research. This research is a result of the numerous fatalities and injuries which occur in the mining industry and which are related to poor operator LOS. Three assessment methods are currently used to assess operator LOS of underground mobile equipment. The light filament (LF) method is a hands-on assessment method that is performed in the field. This method is not evaluated in this paper. The laser scan (LS) method of assessing equipment is a quick and reliable method that comes from the need to evaluate vehicles already located in the field. The computer simulation (CS) method can assess LOS issues using a computer aided drawing (CAD) model, which is useful for assessing current or prototype models. The purpose of the current research is to compare and validate different operator LOS assessment methods. Comparison of the results of the LS and CS visibility plots yielded similar quantifiable results. A visual comparison of the results further illustrate that the LS and CS methods are acceptable assessment tools for mobile equipment operator LOS evaluation. The visibility assessment methods are now being prepared as guidelines for the mining industry to assess current and potential designs.